The Effect of Investment, Free Cash Flow, Earnings Management, and Interest Coverage Ratio on Financial Distress - Meryana; Erna Setiany (Syntax Corporation Indonesia, 2021)
The purpose of this research is to test investments, free cash flow, earnings management, and interest coverage ratio are affecting the risk of financial distress in healthy enterprises.. Healthy companies can be seen from how large the value of working capital, retained earnings, income before tax, market value and sales implemented in the measurement of the financial difficulties model with the Altman Z-score method. Collection of data by purposive sampling and number of samples as many as 33 companies in the category of healthy companies. The results show that free cash flows and interest coverage ratio significant effect on the financial difficulties of healthy companies whereas investment and earnings management had no significant effect on the financial difficulties of healthy companies